How Epistemic Curiosity Influences Digital Literacy: Evidence from International Students in China - Shaojun Ma; Xuan Jin; Xin Li; Hongming Dong; Xuehang Dong; Bowen Tang (Behavioral Sciences)
Digital literacy is the core competitiveness and necessary ability that international students should cultivate while studying in China in the context of education digitalization, and this paper mainly explores whether epistemic curiosity can affect the digital literacy of international students in China. Based on the Technology Acceptance Model, this paper introduces the variable of epistemic curiosity, uses questionnaire survey method and quantitative tools (SPSS and AMOS software) to construct a model of the cognition–perception–formation mechanism of international students’ digital literacy in China, and obtains the following conclusions: Firstly, both interest- and deprivation-type epistemic curiosity can directly promote the digital literacy of international students in China. Secondly, this paper discusses how interest- and deprivation-type epistemic curiosity can affect digital literacy under the mediating effect of perceived usefulness. Finally, perceived ease of use can also indirectly promote the relationship between epistemic curiosity and digital literacy of international students in China. The contribution of this paper is to highlight the formation mechanism of digital literacy in cross-cultural contexts and to explore how interest- and deprivation-type epistemic curiosity affect the digital literacy of international students in China. To a certain extent, this paper reveals the potential process of international students in China to use digital resources to transform into digital literacy and also provides useful evidence for the further development of attractive digital resources.